Importance of an International Registry for and Collaborative Research on Esophageal Atresia - Gottrand, Frédéric; Ley, Delphine; Michaud, Laurent; Sfeir, Rony (Frontiers in Pediatrics, 2017)
Oesophageal atresia (OA) is a rare congenital defect. Data on OA prevalence, management, and long-term outcome are lacking since available data come from small retrospective series from tertiary referral centres. International multicentric registry would provide strong epidemiological data from large population-based cohort on OA prevalence and incidence, treatment, long-term morbidity and prognosis factor, and thus would provide accurate data to evaluate the current guidelines for the OA management. The future challenge of the international network on OA (InoEA) created in 2013 is to promote collaborative database and studies.